PENGARUH KESESUAIAN KOMPENSASI, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP KEADILAN DISTRIBUTIF DI DINAS KABUPATEN BANYUMAS - NANDA PUTRI; Eliada Herwiyanti; Warsidi Warsidi (Jurnal Bisnis dan Akuntansi, 2018)
This research is a quantitative research that was conducted in Banyumas Regency. The purpose of this research is to determine the effect of compensation suitability, organizational commitment and organizational culture to distributive justice. Hypothesis testing in this research using the method of multiple linear regression analysis. The population in this research are all Financial Officer in Banyumas Regency. Samples were taken using purposive sampling technique and Slovin Formula to determining the sample size, thus there are 52 samples in this research. Data was collected trough questionnaires to all of the respondents. Based on the results, it shown that the compensation suitability, organizational commitment, and organizational culture have a positive coefficient on distributive justice. All three independent variables simultaneously influenced to distributive justice, whereas the most influential variable is compensation suitability. It can be conclude that the higher level of compensation suitability, organizational commitment, and organizational culture, the higher level of distributive justice.